Anthropogenic impacts on lakes and measurement of Traphic Level : A comparative study of Ramgarh (Urban) and Chilua (Rural) Lakes of Gorakhpur Districut, U.P. - Singh, Alka; Sharma, V.N. (National Geographical Journal of India, 2022)
Lakes not only provide direct benets like drinking water, irrigation, shes, aquatic crop production, recreation etc. but indirect benets also like, regulation of hydrological cycle, local climate control, maintenance of ecological biodiversity etc. But encroachment and waste disposal, the major anthropogenic activities have determined the lake’s condition and its capability to render the ecological services. Ramgarh and Chilua lakes are ox-bow lakes situated at the centre and north-eastern end of Gorakhpur district respectively in Uttar Pradesh. Both lakes are inuenced by anthropogenic activities of encroachment and waste disposal. Respective toposheets and google earth images are used to trace out the encroachments. The eld survey was executed in 2018 to locate the waste disposal points and to collect samples and trophic status index measured using Carlson index. The quality and volume of water of Ramgarh Lake were good, as per local people, up to 1980s while Chilua lake it had maintained it up to 2005, but thereafter, human impacts have pushed the lakes at the edge of depletion. During 1922 to 2018, about 34.16 per cent area of Ramgarh lake (urban) and 24.93 per cent area of Chilua lake (rural) had been occupied by people for different purposes. The urban (Ramgarh) lake water quality is eutrophic to hyper-eutrophic and rural (Chilua) lake water is mesotrophic to eutrophic due to rapid unplanned urbanization, commercial layouts and agricultural practices. Encroachment in lake areas, sewage and waste disposal, depletion of water quality, excess exploitation of biota from the lakes had been seen as deteriorating factors. Alterations in ecological integrity were evident from reduced water containing capacity, the ash of oods, contaminated water, obnoxious odour, copious growth of invasive oating macrophytes, the disappearance of native sh species, increased breeding ground for mosquito and other disease-causing parasites due to untreated sewage intake.